Efficiency pricing parameters for project appraisal in South Africa (textiles and clothing) - Stefano Mainardi (South African Journal of Business Management, 1998)
In developing economies, market prices do not reflect relative scarcities and the fiscal system alone is less than adequate for the achievement of efficiency and equity goals. The use of economic, and eventually social, project appraisal continues to be a necessary policy instrument. Following the OECD-World Bank method of economic cost-benefit analysis, the article presents estimates of efficiency pricing parameters relative to two manufacturing sectors in South Africa. These estimates are partly based on medium-term policy options and projections. The choice of a sectoral, rather than a national, focus is explained by the effects of current policy reforms, which affect among others a complex trade regime, and by a varied production structure.
Keywords: 650